Role of ADAMTS-5 in Aortic Dilatation and Extracellular Matrix Remodeling. Issue 7 (July 2018) - Fava, Marika; Barallobre-Barreiro, Javier; Mayr, Ursula; Lu, Ruifang; Didangelos, Athanasios; Baig, Ferheen; Lynch, Marc; Catibog, Norman; Joshi, Abhishek; Barwari, Temo; Yin, Xiaoke; Jahangiri, Marjan; et al.
Abstract : Objective—: Thoracic aortic aneurysm (TAA), a degenerative disease of the aortic wall, is accompanied by changes in the structure and composition of the aortic ECM (extracellular matrix). The ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family of proteases has recently been implicated in TAA formation. This study aimed to investigate the contribution of ADAMTS-5 to TAA development. Approach and Results—: A model of aortic dilatation by AngII (angiotensin II) infusion was adopted in mice lacking the catalytic domain of ADAMTS-5 (Adamts5 Δcat ). Adamts5 Δcat mice showed an attenuated rise in blood pressure while displaying increased dilatation of the ascending aorta (AsAo). Interestingly, a proteomic comparison of the aortic ECM from AngII-treated wild-type and Adamts5 Δcat mice revealed versican as the most upregulated ECM protein in Adamts5 Δcat mice. This was accompanied by a marked reduction of ADAMTS-specific versican cleavage products (versikine) and a decrease of LRP1 (low-density lipoprotein-related protein 1). Silencing LRP1 expression in human aortic smooth muscle cells reduced the expression of ADAMTS5, attenuated the generation of versikine, but increased soluble ADAMTS-1. A similar increase in ADAMTS-1 was observed in aortas of AngII-treated Adamts5 Δcat mice but was not sufficient to maintain versican processing and prevent aortic dilatation. Conclusions—: Our results support the emerging role of ADAMTS proteases in TAA. ADAMTS-5 rather than ADAMTS-1 is the key protease for versican regulation in murine aortas. Further studies are needed to define the ECM substrates of the different ADAMTS proteases and their contribution to TAA formation. Abstract : Supplemental Digital Content is available in the text.